Dispute resolution & crisis management - Tancangco, Danilo L. (Quezon City : Wisemans Books Trading, Inc., 2022)
"Intended mainly as a steer to a flourishing performance of the police law enforcement's duties and responsibilities. This steer on dispute resolution and crisis/incident management has the prospective to inspire law enforcers to value the awareness of professionalism."
English text.
Keywords: Incident management